2019
DOI: 10.1007/s00125-019-04984-w
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic alterations in pancreatic lymph node stromal cells from human donors with type 1 diabetes and NOD mice

Abstract: Aims/hypothesis Tolerance induction in lymph nodes can be mediated by both haematopoietic cells (e.g. specific dendritic cells subsets) and by non-haematopoietic cells (e.g. lymph node stromal cells [LNSCs]) when they present peripheral tissue antigens to autoreactive T cells. LNSCs normally regulate T cell trafficking and survival and help to maintain peripheral tolerance by exerting immunosuppressive effects. However, whether autoimmunity can be associated with defective tolerogenic functions of LNSCs is unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Next to possible antigen presentation by LNSCs, we demonstrated in this study that human LNSCs possess an arsenal of immunomodulatory molecules both in vitro on cultured human LNSCs and ex vivo on freshly isolated human LNSCs. As previously reported, PD-L1 expression is mostly restricted to endothelial cells (LECs and BECs) on freshly isolated human LN [59]. Similarly, our data also showed that PD-L1 protein expression was higher on endothelial cells in comparison to FRCs and DNs.…”
Section: Discussionsupporting
confidence: 91%
“…Next to possible antigen presentation by LNSCs, we demonstrated in this study that human LNSCs possess an arsenal of immunomodulatory molecules both in vitro on cultured human LNSCs and ex vivo on freshly isolated human LNSCs. As previously reported, PD-L1 expression is mostly restricted to endothelial cells (LECs and BECs) on freshly isolated human LN [59]. Similarly, our data also showed that PD-L1 protein expression was higher on endothelial cells in comparison to FRCs and DNs.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, FRCs modulated their interactions with autoreactive T lymphocytes by remodeling their reticular network in LNs; PTAs and podoplanin played a central role and their alterations may favor T1D [ 21 ]. These findings are supported by a previous study from the same group that investigated alterations in pancreatic lymph nodes from humans and mice [ 52 ]. Kasinath et al studied crescentic glomerulonephritis (GN), an autoimmune inflammatory condition characterized by the rapid deterioration of kidney function.…”
Section: Discussionsupporting
confidence: 88%
“…More importantly, we recently reported that stromal cells in the PLNs of T1D patients (the same lymph nodes as those targeted by mRNA-NPs after i.p. in mice) had higher antigen presentation and tolerogenic potential than those in control individuals 55 . Thus, the ability to target antigens to LNSCs with mRNA-NPs as shown here is therapeutically relevant.…”
Section: Discussionmentioning
confidence: 69%